Echoes of the Unconscious: Freudian and Modernist Readings of Dr. Jekyll and Mr. Hyde - Raquel Correia de Souza, (VIA PANORAMICA: Revista de Estudos Anglo-Americanos / A Journal of Anglo-American Studies, 2025)
ABSTRACT: Considering Robert Louis Stevenson’s The Strange Case of Dr. Jekyll and Mr. Hyde, the present article aims to analyze the novella through the lens of Freudian psychoanalytic theory and modernist literary elements. Additionally, this article situates Stevenson’s work within a broader context of modernist literature by examining its exploration of critiques of Victorian moral rigidity and the fragmented identity. The novella’s use of Uncanny elements, unconscious mind and other concepts later developed by Freud highlights its avant-garde nature that also offers a narrative that delves into the psychological depth of the human mind. This article underscores the significance of Dr. Jekyll and Mr. Hyde not only as a timeless exploration of human nature and social expectations but also reveals its contribution to both psychological literature and modernist narrative techniques.